RESTRUCTURING INDONESIAN RAILWAY – INTEGRATION OR SEPARATION - Utut Widyanto; Siti Malkhamah (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2013)
Law No. 23/2007 on Railways is opening the option for private sector or Local Government to be involved in railways. This study investigated experiences from other countries in railway restructuring especially their measures and model of restructuration. The countries investigated are Germany, Japan, Britain, and Sweden. After investigating restructuration experiences from other countries and looking on Indonesian railway condition, the study developed two approach of restructuration.The first approach of restructuration was using vertical separation model. The approach has advantages of: eliminating potential discrimination from the current holding company, increase the transparency in railway fund management, and more competitive market. The disadvantages were the high transaction costs, a need for monitoring of the other’s performance, the difficulty in creating complex performance schedules. The second approach was using the integration model. It has advantages of lower transaction cost, easy to manage path allocation, and efficient scheduled design. The disadvantages were the misuse railway fund allocation, also potential discrimination to the new entrants.The study found that the separation model is still the best approach for restructuring Indonesian railway but if looking at the Indonesian railway current condition with its problem of backlog assets it would be better that the separation approach is used in the development of railway in other islands.Keywords: Restructuration, separation, funds, operator.